Effects of the inclusion of physical activity in secondary education academic classes on educational indicators and health markers: rationale and methods of the ACTIVE CLASS study - González-Pérez, María; Sánchez-Oliva, David; Grao-Cruces, Alberto; Cano-Cañada, Enrique; Martín-Acosta, Fátima; Muñoz-González, Raúl; Bandera-Campos, Francisco J.; Ruiz-Hermosa, Abel; Vaquero-Solís, Miguel; Padilla-Moledo, Carmen; Conde-Caveda, Julio; Segura-Jiménez, Víctor; et al. (Frontiers in Public Health, 2024)
Background Increasing physical activity (PA) levels and reducing sedentary behaviors in children and adolescents is a need, especially in schools. Active breaks and physically active learning are examples of two emerging methodologies that have been shown to be effective in increasing PA levels and additionally produce improvements in children’s educational markers. However, the evidence in adolescents is very limited. This paper presents the design, measurements, and interventions implemented in the ACTIVE CLASS study, whose objectives are: (i) evaluate the effects of two interventions on PA levels, sedentary time, health-related physical fitness academic indicators, cognition, and markers of psychological health among secondary education students; (ii) evaluate teachers’ and students’ experiences about the implementation of these the two school-based PA intervention. Methods A randomized controlled study is conducted with a total of 292 students aged 12–14 years old from six schools (7th and 8th grade) in Spain (three in Cadiz and three in Caceres). One school from each study provinces is randomly assigned to either the active break intervention group, the physically active learning intervention group, or the control group. The interventions have a duration of 16 weeks. Nine main measurement categories are assessed: PA and sedentary time, health-related physical fitness, academic indicators, cognition, psychological health, motivational variables, dietary patterns, sociodemographic characteristics, as well as qualitative information through semi-structured individual interviews and focus groups. Three independent measurements of evaluation are distinguished: pre-intervention, post-intervention (week 16) and retention measurement (4 weeks after the intervention). For quantitative variables, descriptive, correlational, regression and repeated measures ANOVA will be applied. Discussion To the best of our knowledge, the ACTIVE CLASS study is the first of its kind in Spain to evaluate the effects of incorporating active breaks and physically active learning in secondary education. In addition, this project provides important information on the effects of two school-based PA intervention arms on educational variables and health markers in adolescents. This will provide valuable and innovative training to the educational community, enabling them to implement teaching methodologies that have the potential to enhance academic performance and improve the quality of life for their students. Clinical trial registration clinicaltrials.gov, NCT05891054.